SMALL INDUSTRY IN EAST JAVA: PROBLEM ANALYSIS AND SOLUTIONS - Endang Siswati; Sofiah Nur Iradawati; Nurul Imamah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this research is to analyze the problems and find solutions to the problems of small industries in East Java. This research is a qualitative descriptive study using interviews and observations of six small industries in East Java. The data obtained from the interview results were then triangulated. The results of the study found that the problem of difficulties with imported raw materials was tackled by using several suppliers, while industries that used local raw materials did not experience difficulties with raw materials. Small industry capital problems use their own capital, capital from banks and cooperation capital. Regarding the low competence of Human Resources, small industries can conduct training, carry out recruitment and selection strictly. Regarding product marketing, the company markets its products offline and online. The problem is that many small industries have not standardized their products, companies can continue to improve in an effort to achieve standard